THE EFFICIENCY OF INITIAL PHASE TREATMENT IN CHRONIC MARGINAL PERIODONTITIS - Adriana Monea; Diana Pop; Gabriela Beresescu (European Scientific Journal, ESJ, 2014)
Aim of the study. To evaluate the efficiency of initial periodontal treatment by measuring indices of oral hygiene, gum inflammation and periodontal pocket depth before and after treatment. Material and methods. 20 adult subjects were included in the study. Clinical examination included measurements of attached gingiva width, gum inflammation (GI), oral hygiene (OHI), periodontal pocket depth (PD), gingival recession (GR) and tooth mobility. The treatment had consisted of plaque control, supra- and subgingival scaling and root planing (SPR). Treatment success was quantified by measuring of the above indices before and after treatment. Results. OHI values decreased with 28,64% after DRP and GII decreased with 51,11%. From the total of 1289 sites with values ≥4mm, 512 sites got normal values at probing after initial treatment, the rest of 777 sites still had pathologic values, requiring further pocket reduction treatment. Conclusions. Initial therapy is the only therapy needed for patients with superficial periodontal disease, but patients with aggressive or deep forms of periodontitis would require further pocket depth reduction treatment.